Experimental Manipulation of Guided Attention to the Shoulder Movement Task in Clinical Dohsa-hou Induces Shifts in the Reactive Mode and Indicates Flexible Cognitive Control Performance - Fujikawa, Takuya; Kabir, Russell Sarwar; Haramaki, Yutaka (Frontiers in Psychology, 2022)
The empirical basis for self-control in Dohsa-hou as it relates to effects on cognitive processes has been explored in a few studies of the Japanese psychotherapy, but not under standardized conditions with a strong predictive theory of control. This study reports on a series of experiments with the Dual Mechanisms of Control framework to clarify the possible regulatory mechanism of Dohsa-hou by focusing on shoulder movement, a key body movement task used by practitioners across applied settings. Cognitive control was operationalized with the AX version of Continuous Performance Test (AX-CPT) paradigm for proactive control and a modified Stroop task paradigm for reactive control in a 3-arm parallel group trial study design. Healthy Japanese university students were assigned to a Dohsa-hou group that performed a shoulder movement task for few minutes, an active control group that performed a similar task, or a passive control group comprised of a resting condition. A total of fifty-five participants performed the AX-CPT and fifty-seven participants performed the modified Stroop task before and after the group manipulation. In the AX-CPT, an increase in the error rate of AY (true cue-false probe) trial from pre- to post-test was observed in the passive control group only, and found to be marginally higher in the passive control group relative to Dohsa-hou group at post-test. This indicated that Dohsa-hou moderated the activation of proactive control by repeated AX-CPT performance. The error rate of the Proactive Behavioral Index did not differ from zero at post-test only in the Dohsa-hou group, indicating flexible cognitive control. In the modified Stroop task, there was no difference between congruent and incongruent trials at post-test for the Dohsa-hou group only, indicating the facilitation of reactive control. The evidence for a balancing effect for the Dohsa-hou-based shoulder movement task indicates that clients experience a form of continuous self-monitoring, which might reduce mind-wandering from their focus on movement execution combined with iterative verbal feedback from the therapist. Overall, the results of the present study suggest that the self-regulatory mechanism promoted in clinical Dohsa-hou emphasizes guided shifts in attention to the reactive mode toward a balance of cognitive control.